The effectiveness of library orientation program in reducing library anxiety among undergraduate students Faculty of Information Management at the UiTM Puncak Perdana / Anis Aziyah Azhar - Azhar, Anis Aziyah (2013)
The purpose of this study is to examine the effectiveness of library orientation program in reducing library anxiety among the undergraduate students of the Faculty of Information Management at the UiTM Puncak Perdana Library. The objectives of this study are to determine the effectiveness of library orientation program, to identify the factors that cause library anxiety among the students and to discover the students' awareness toward library services. Various articles related to the topic are taken from various sources. The questionnaire was distributed to 260 target respondents which consist of undergraduate students from semester 1, semester 2 and semester 3 of the Faculty of Information Management. After the results were obtained, the researcher used SPSS version 16.0 to analyze the data. The results revealed that the majority of respondents agreed that library orientation program offers awareness of library services enhances their skills and helps students to find information quickly and easily. Besides that, some discussions will be discussed about the issues based on the results. This study had a profound impact on making recommendations for the academic library field. The study concluded that the library orientation program are very important because they may help reducing library anxiety and to encourage students' skills and knowledge in searching for information. The findings of this study would be beneficial for library management to evaluate the effectiveness of the library orientation program.